Sensitivity to Inflectional Morphemes in the Absence of Meaning: Evidence from a Novel Task - Cilibrasi, Luca; Stojanovik, Vesna; Riddell, Patricia; Saddy, Douglas (Journal of psycholinguistic research, 2019)
A number of studies in different languages have shown that speakers may be sensitive to the presence of inflectional morphology in the absence of verb meaning (Caramazza et al. in Cognition 28(3):297-332, 1988; Clahsen in Behav Brain Sci 22(06):991-1013, 1999; Post et al. in Cognition 109(1):1-17, 2008). In this study, sensitivity to inflectional morphemes was tested in a purposely developed task with English-like nonwords. Native speakers of English were presented with pairs of nonwords and were asked to judge whether the two nonwords in each pair were the same or different. Each pair was composed either of the same nonword repeated twice, or of two slightly different nonwords. The nonwords were created taking advantage of a specific morphophonological property of English, which is that regular inflectional morphemes agree in voicing with the ending of the stem. Using stems ending in /l/, thus, we created: (1) nonwords ending in potential inflectional morphemes, vɔld, (2) nonwords without inflectional morphemes, vɔlt, and (3) a phonological control condition, vɔlb. Our new task endorses some strengths presented in previous work. As in Post et al. (2008) the task accounts for the importance of phonological cues to morphological processing. In addition, as in Caramazza et al. (1988) and contrary to Post et al. (2008), the task never presents bare-stems, making it unlikely that the participants would be aware of the manipulation performed. Our results are in line with Caramazza et al. (1988), Clahsen (1999) and Post et al. (2008), and offer further evidence that morphologically inflected nonwords take longer to be discriminated compared to uninflected nonwords.
Keywords: dospělí; Female; Phonetics; reakční čas; Adult; mladý dospělý; ženské pohlaví; lidé; percepce řeči; Speech Perception; Psycholinguistics; Male; Young Adult; Reaction Time; psycholingvistika; mužské pohlaví; fonetika; diskriminace (psychologie); Discrimination, Psychological; Humans